Responding to Global Learning Needs during a Pandemic: An Analysis of the Trends in Platform Use and Incidence of COVID-19 - Heini Utunen; Richelle George; Ngouille Ndiaye; Melissa Attias; Corentin Piroux; Gaya Gamhewage (MDPI AG, 2020)
On 11 March 2020, the World Health Organization (WHO) declared the outbreak of coronavirus disease (COVID-19) to be a pandemic. As a result, the OpenWHO.org online platform, which serves as WHO's learning hub for emergencies, was tested for the first time on its core purpose of scaling up trusted public health information in a global emergency. This descriptive study examines and documents the WHO learning response in the early months of the pandemic by comparing epidemiological information and OpenWHO.org use in the countries with the highest COVID-19 cases. Statistical datasets from OpenWHO.org and WHO's COVID-19 dashboard were overlaid for the period 11 March-22 May 2020. During this period, for most of the 24 countries with the highest COVID-19 cases, platform use showed a corresponding trend. Courses published in the official languages spoken in these countries were well utilized, indicating a need to produce materials in languages spoken by affected communities. Of the countries with the highest number of users on OpenWHO, only half were top users of the platform before the pandemic. The existence of an established online platform for health emergencies assisted WHO in massively and quickly scaling up the dissemination of essential learning materials for COVID-19.